تعليم النحو لغير العرب: الأسس والمبادئ - khoirurrijal khoirurrijal (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
The education is not only a transfer of information and knowledge to the recipient, but also must be conversant and based role in the educational process, it makes a vibrant curriculum, tribal upon the students with all the passion and fun and interest are investigating. Teacher is the one who helps his disciples to save, store and retrieve what is necessary information, which is who is qualified educationally and psychologically, who knows foundations and educational principles, which chooses the best ways to suspense disciples in the educational process and so on. But, as almost exclusively is understood by the latecomers of scientists at the base to aware of when looking for constructive or the science standards derived from the extrapolation of the words Arab’smistakes in the installation. So, the good foundations and principles of teaching are very important to get succsess in the teaching and education’s activities as we hope. Education, foundations and principles of education.